The Effect of Mindfulness Implementation on the Concentration Ability of Early Childhood - Milna Juwita; Syamsuardi; Tasrif Akib; Arie Martuty; Intisari; Nur Alim Amri (Jurnal Pendidikan Anak Usia Dini Undiksha, 2025)
Young children often have difficulty concentrating and are easily distracted, which hinders their learning and cognitive development. According to Piaget's theory, the concentration of 5- to 6-year-olds is influenced by their ability to shift their attention. This study aims to evaluate the effect of implementing mindfulness on improving concentration in young children. Mindfulness is defined as a full awareness approach that involves activities such as breathing exercises, meditation, and environmental observation. The study uses a pre-experimental method with a "One Group Pretest-Posttest" design, involving 16 children aged 5-6 years. Mindfulness was applied over six sessions, with measurements of children's concentration before and after the treatment, which included simple breathing exercises, listening to nature sounds, and observing objects with full attention. The results showed a significant improvement in children's concentration after the mindfulness intervention. This indicates that mindfulness helps children to focus more and manage their attention better. Therefore, mindfulness is an effective approach to enhancing concentration in young children and supporting their cognitive development. The implementation of mindfulness is highly recommended in early childhood education as a strategy to optimize learning potential and should be applied more widely in early childhood education settings.